PERBANDINGAN PENGETAHUAN, SIKAP DAN PERILAKU SISWI TERHADAP KANKER PAYUDARA DI SMAN 1 MATUR DENGAN SMAN 4 BUKITTINGGI TAHUN 2017 - Yuliza Anggraini (Menara Ilmu, 2018)
Breast cancer is one of three series of malignancy that attacks women inIndonesia, namely breast cancer, cervical cancer and skin cancer. In WestSumatra, the incidence of breast cancer is 5.6% this figure is higher than thenational average of only 4.3%, putting West Sumatra sixth out of 33 provinces inIndonesia. This research was conducted with quantitative approach withcomparative design. The results obtained from this study is that the knowledge,attitude and behavior of female students to breast cancer in SMAN 1 Matur isvery different from SMAN 4 Bukittinggi. A significant difference exists in theknowledge and behavior while the attitude of female students both have a goodattitude toward breast cancer.Keywords: Knowledge, Attitude, Behavior, Breast Cancer